Spatial analysis of cultural activities in the microregions of Minas Gerais - Amir Borges Ferreira Neto; Fernando Salgueiro Perobelli (EconomiA, 2013)
This paper aims at the evaluation of cultural activity aspects from the 66 microregions of the state of Minas Gerais by creating a comparable index, the DPCA, and by detecting spatial patterns in this index using Exploratory Spatial Data Analysis (ESDA). To study the aspects of cultural activities we calculated the DPCA index using factorial analysis. The database used was the Basic Municipal Information developed by IBGE. The methodology enables the construction of a Development Potential of Cultural Activities (DPCA) index composed by three factors that allow us to evaluate the aspects of cultural activities: one comprising cultural activities and structure, one comprising means of access to culture and another comprising cultural management. Some conclusion that can be highlighted is the low result of the Development Potential of Cultural Activities (DPCA) for 64 from the 66 microregions. Regarding the ESDA, we find cultural clusters when the calculus are performed for PDAC individually and for a comparison with the GDP. – – Este trabalho teve por objetivo avaliar aspectos da atividade cultural das 66 microrregi\~oes do estado de Minas Gerais a partir da criaç\~ao de um índice comparativo, o PDAC, e detectar os padr\~oes espaciais do referido potencial das atividades culturais no estado. O estudo dos aspectos da atividade cultural foi realizado utilizando a análise fatorial. Esta foi implementada tomando por base o anexo cultural da Pesquisa de Informaç\~oes Básicas Municipais do IBGE. A introduç\~ao da quest\~ao espacial foi realizada a partir da Análise Exploratória de Dados Espaciais (AEDE). Como principais resultados destacam-se a formaç\~ao de três fatores, que em conjunto formam o Potencial de Desenvolvimento das Atividades Culturais (PDAC) e que permitem avaliar os aspectos da atividade cultural: um de atividades e estrutura cultural, um de meios de acesso e outro de gest\~ao cultural. Outro resultado que merece a atenç\~ao é o baixo Potencial de Desenvolvimento das Atividades Culturais (PDAC) de 64 das 66 microrregi\~oes do estado. Em relaç\~ao a AEDE ressalta-se a formaç\~ao de clusters culturais quando analisada a variável PDAC individualmente e comparativamente com o PIB.
Keywords: Z10; R10; 330; Exploratory Spatial Data Analysis; Cultural economics; Minas Gerais